The consequences of changing conditions of the European dairy sector for the strategies of dairy companies - Weindlmaier, Hannes (Acta agriculturae Slovenica, 2004)
This contribution deals with the consequences of changing conditions of the European dairy sector. Important influences discussed are the decisions of the Mid-Term-Review of the Common Agricultural Policy, the enlargement of the European Union to include the countries of Central and Eastern Europe and the concentration and globalisation of the food trade. Based on these changes, the dairy industry has to adjust their strategies. Of great importance for future competitiveness is the size of dairy companies and plants, as large enterprises and plants have several economic advantages, if an optimal size corresponds with a good job performed by the management of the company. Important alternative strategies like the cost leadership strategy, the differentiation strategy, the focus strategy and internationalisation are discussed and assessed with respect to their possible contribution to retain respectively to improve competitiveness of dairy enterprises. It is concluded that within a period of ten years the face of the European dairy sector will change quite extensively. Only those enterprises will survive which in time actively implement strategies, which are a suitable answer to the changing conditions.
Keywords: mlekarstvo; pogoji; European Union; Evropska unija; globalizacija; globalization; konkurenčnost